2004
DOI: 10.1073/pnas.0402642101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity enhances the resistance of a seagrass ecosystem to disturbance

Abstract: Motivated by recent global reductions in biodiversity, empirical and theoretical research suggests that more species-rich systems exhibit enhanced productivity, nutrient cycling, or resistance to disturbance or invasion relative to systems with fewer species. In contrast, few data are available to assess the potential ecosystemlevel importance of genetic diversity within species known to play a major functional role. Using a manipulative field experiment, we show that increasing genotypic diversity in a habita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
701
10
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 694 publications
(756 citation statements)
references
References 36 publications
(44 reference statements)
36
701
10
9
Order By: Relevance
“…Other recent work supports a role for genotypic diversity, particularly under disturbance (35). Whereas that study found only transient effects after intense bird grazing, we find strong effects that persist over at least one growth period.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Other recent work supports a role for genotypic diversity, particularly under disturbance (35). Whereas that study found only transient effects after intense bird grazing, we find strong effects that persist over at least one growth period.…”
Section: Discussionsupporting
confidence: 73%
“…This result contrasts markedly with several independent experiments that used a similar planting technique during normal climatic conditions; these experiments consistently showed low mortality and a 3-fold increase in shoot density from May through August (30,34), making it unlikely that transplant shock was responsible for this decline (but see ref. 35). During the first major warming event at the beginning of June, unusual signs of heat-stressrelated mortality were already present (discolored meristems, root necrosis, and leaf loss).…”
Section: Resultsmentioning
confidence: 99%
“…At the patch and population level, increasing genetic diversity (e.g. number of genotypes) increases diversity of associated arthropod communities, confers greater resilience to biotic and abiotic stressors, and affects key aspects of ecosystem function [21,27,28,[31][32][33][34][35]. Recently, studies have begun to extend the scope of community genetics research to examine how genetic variation and population divergence within herbivorous insects, endosymbionts [36][37][38] and predaceous fishes [39][40][41][42] have cascading bottom-up and topdown effects within communities.…”
Section: Introductionmentioning
confidence: 99%
“…Still, even among marine studies, confounded variation in systems and methodologies hampers efforts to explain differences in outcome. Although longer-term studies do tend to find strong effects, these studies are also from colder temperate regions, are conducted intertidally, and are in the field (14)(15)(16). In contrast, studies that find weak or no effects often involve subtidal taxa and are shorter term and/or conducted in mesocosms (7,8,17).…”
mentioning
confidence: 99%